Diet of post-breeding Antarctic Shags Phalacrocorax bransfieldensis at Cockburn Island, Antarctic Peninsula - Beltrán, Marianela; Tavella, Gabriela Nelly; Casaux, Ricardo Jorge
The diet of post-breeding Antarctic shags (Phalacrocorax bransfieldensis) was investigated at Cockburn Island, in the Antarctic Peninsula, through the analysis of pellets collected in February 2015. Demersal-benthic fish were the most frequent and important prey, followed by invertebrates. Among the fish, nototheniids were most abundant in the diet in terms of numbers, whereas channichthyids, Chionodraco rastrospinosus in particular, represented most of the mass. The information provided here differs from that reported for post-breeding individuals belonging to other shag species and for post-breeding Antarctic shags. This article discusses our results and the differences with previous studies, in terms of prey availability among localities. Fil: Beltrán, Marianela. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Centro Nacional Patagónico. Centro para el Estudio de Sistemas Marinos; Argentina Fil: Tavella, Gabriela Nelly. Secretaría de Turismo y Áreas Protegidas; Argentina Fil: Casaux, Ricardo Jorge. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Patagonia Norte. Centro de Investigación Esquel de Montaña y Estepa Patagóica. Universidad Nacional de la Patagonia Argentina. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina